Bariatric surgery in elderly patients - Alexander V. Smirnov; Vladimir R. Stankevich; Ekaterina S. Danilina; Vladislav I. Sychev; Evgeniya M. Voronets; Vladimir I. Sharobaro; Nikolay A. Solovyev; Yury V. Ivanov; Robert I. Khabazov (Клиническая практика)
BACKGROUND: Bariatric surgery is indicated to patients with morbid obesity and aged 18–60 years. In older aged patients, such surgery can also be taken into consideration, however, the procedure of selecting the patients is not included into the clinical recommendations, which determines the topicality of the research. AIM: To establish a protocol for surgical treatment of morbid obesity in patients older than 60 years. METHODS: The research included 800 patients operated during the period of 2018–2023 at the Federal State Budgetary Institution “Federal Scientific and Clinical Center” of the Federal Medical-Biological Agency of Russia due to the presence of morbid obesity, of which 38 had an age of 61 and older. All the patients underwent only two types of surgery — laparoscopic longitudinal resection and laparoscopic Roux gastric bypass surgery. All the patients of the older age group underwent personalized selection for surgical treatment, screening procedures were arranged in order to detect the senile asthenia syndrome and, retrospectively, to stratify them using the GeriBari prognostic scale. During one year of follow-up, the remote results were assessed in all the patients along with the quality of life. RESULTS: There were no postoperative complications in the older age group, the 30-day mortality was 2.6% (1 patient has died from the complications of the coronaviral infection). The weight loss was found to be significantly less in the older age group (61 and older) comparing to the main group of patients (18–60 years): for laparoscopic longitudinal resection — 55.5% versus 73%, respectively (р=0.01), for laparoscopic Roux gastric bypass surgery — 58% versus 77.5% (р=0.0008). The remission of type 2 diabetes was achieved in 70.6% of the patients of the older age group. The quality of life among the patients of the older age group, even with the slight decrease of the excess body weight, was significantly better 12 months after surgery. CONCLUSION: Among the elderly patients with morbid obesity, it is possible to perform bariatry surgeries safely and effectively when following the proposed protocol.